Analisis Hukum Standar Akreditasi Terhadap Sertifikat Halal Luar Negeri Perspektif Fatwa MUI Nomor 4 Tahun 2003 Tentang Standardisasi Fatwa Halal - Dewi, Almira Kemala; Tarigan, Tetty Marlina (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Imported products in Indonesia have been highly developed and become people's needs such as food, cosmetics, medicines, and so on. There are so many imported products that attract the attention of consumers because of the rapid and easily accessible advances in technology and information for consumers. However, the large number of imported products that are distributed to various places in Indonesia are not in accordance with the regulations. Islam obliges its people to consume/use halal products and stay away from all unclean products. The problem is, how is the enforcement of halal certificates for imported products in Indonesia based on the MUI fatwa number 4 of 2003. This study uses a normative juridical research method with a statutory approach and analyzes literature sources related to this research. From the results of the author's research, it was found that many products had received halal certification from the country of origin but did not register them with the Halal Product Assurance Organizing Agency (BPJPH). So it can be concluded that imported products that are halal certified in the country of origin, if they have made adjustment cooperation with Indonesia, do not apply for halal certificates in Indonesia again, but register at the Halal Product Assurance Organizing Agency or abbreviated as BPJPH (which is under the auspices of the Ministry of Religion) to get a halal registration number to comply with the Standard Operating Procedure (SOP) contained in the MUI Fatwa.